2006
DOI: 10.1093/heapro/dal034
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a national programme to reduce inappropriate use of antibiotics for upper respiratory tract infections: effects on consumer awareness, beliefs, attitudes and behaviour in Australia

Abstract: The over-use of antibiotics, in particular, inappropriate use to treat upper respiratory tract infections (URTIs), is a global public health concern. In an attempt to reduce inappropriate use of antibiotics for URTIs, and, in particular, to modify patient misconceptions about the effectiveness of antibiotics for URTIs, Australia's National Prescribing Service Ltd (NPS) has undertaken a comprehensive, multistrategic programme for health professionals and the community. Targeted strategies for the community, via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
101
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(102 citation statements)
references
References 23 publications
1
101
0
Order By: Relevance
“…The benefits of public campaigns present slowly over time, suggesting the need for continual reinforcement and repetition (Wutzke et al, 2006). Strategies including use of television, newspapers, and the internet are effective modalities for public education, considering transferring time zone (Finch, Metlay, Davey, & Baker, 2004;Madle, Kostkova, Mani-Saada, Weinberg, & Williams, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The benefits of public campaigns present slowly over time, suggesting the need for continual reinforcement and repetition (Wutzke et al, 2006). Strategies including use of television, newspapers, and the internet are effective modalities for public education, considering transferring time zone (Finch, Metlay, Davey, & Baker, 2004;Madle, Kostkova, Mani-Saada, Weinberg, & Williams, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Repeated information using short, tailored slogans and cues to action would improve general knowledge on antibiotics, especially in groups with lower educational levels (Marx, Nedelmann, Haertle, Dieterich, & Eicke, 2008). Furthermore, if the aim is to reduce antibiotic use for URIs, then public education would work best when aligned with interventions aimed at physicians (Kiang et al, 2005;Wutzke et al, 2006). Educational campaigns including physicians have had a positive effect on knowledge and a reduction in the prescription of antibiotics (Kiang et al; Wutzke et al).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][22] Most campaigns show around 10% reductions in prescriptions and appear effective only in the short-run. 23,24 Multi-faceted campaigns that target both prescribers and consumers appear to yield better results than more narrowly designed interventions. 25 Amongst the most promising policy options in primary care is "backup/ delayed prescribing" which describes interventions that create a delay for patients between prescription and the collection of antimicrobials for infections.…”
Section: Responsible Use By Healthcare Workersmentioning
confidence: 99%
“…45 An evaluation of EAAD effectiveness in the UK for instance concluded that the campaign had only led to a minimal increase in public awareness, with no observable reduction in antibiotic use. 46 However, long-running campaigns, especially in Australia and France, have been associated with modest but consistent improvements in consumer awareness, as well as a reduction in antibiotic prescribing.. 47,24 What has proved to be particularly challenging is communicating the differences between bacterial and viral infections. 30,48 Case study 1: The physican and patient perspective -how failure to engage the private sector in AMR control can impact health A 43-year old male patient with a past history of tuberculosis infection presented at a tertiary care centre in Karachi, Pakistan, with a one-month history of hemoptysis, fever and weight loss.…”
Section: Responsible Use and Public Awarenessmentioning
confidence: 99%